2022
DOI: 10.1037/pst0000420
|View full text |Cite
|
Sign up to set email alerts
|

A latent trajectory analysis of inpatient depression treatment.

Abstract: Patients seeking psychotherapy may progress through treatment in varying ways. Modeling multiple treatment trajectories through growth mixture modeling provides a comprehensive way of understanding a patient population. Multiple trajectories may additionally help researchers describe complexities within a patient population, such as those with severe and persistent disorders and comorbid symptoms, to understand characteristics of patients that may be struggling during treatment. We analyzed the depression symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…In this study the intensive inpatient psychotherapy treatments provided were affect phobia therapy (APT) and VITA. These specific inpatient treatments have previously been described by Ulvenes et al [ 27 ]. The patients in the wait list control group received TAU in their local communities.…”
Section: Methodsmentioning
confidence: 99%
“…In this study the intensive inpatient psychotherapy treatments provided were affect phobia therapy (APT) and VITA. These specific inpatient treatments have previously been described by Ulvenes et al [ 27 ]. The patients in the wait list control group received TAU in their local communities.…”
Section: Methodsmentioning
confidence: 99%
“…We report on the determination of the sample, all data exclusions, and manipulations. Data from a different, but overlapping sample from the same unit are reported in two separate publications (Melsom et al, 2022; Ulvenes et al, 2022). The analysis was performed with the statistical program R (R Core Team, 2020) using the lavaan package (v.0.6-9; Rosseel, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…We report on the determination of the sample, all data exclusions, and manipulations. Data from a different but overlapping sample from the same unit is reported in a separate publication (Ulvenes et al, 2022). The analysis was conducted in the statistical program R (R Core Team, 2020) using the lavaan package (v0.6-7; Rosseel, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, these results indicate that tolerance of emotional distress may be a mechanism of change in the treatment of depression. Relatedly, Ulvenes et al (2022) analyzed a large sample of chronically depressed patients and found that patients who did not respond to treatment had more severe difficulties with tolerance of emotional distress than those who responded to treatment. Thus, it can be hypothesized that tolerance of emotional distress is a particularly important factor in chronic depression.…”
mentioning
confidence: 99%